Identification of diaminopimelic acid in the Legionnaires disease bacterium. - Guerrant, G O (1979)
Diaminopimelic acid was found to be a component of the cell wall of the Legionnaires disease bacterium, thus providing additional evidence that the organism is a bacterium. The presence of this amino acid was determined by gas-liquid chromatography and confirmed by gas chromatography-mass spectrometry.